Effects of Increasing Standardized Ileal Digestible Lysine During Gestation on Growth and Reproductive Performance of Gilts and Sows Under Commercial Conditions - L. L. Thomas; L. K. Herd; R. D. Goodband; S. S. Dritz; M. D. Tokach; J. C. Woodworth; J. M. DeRouchey; M A Gonçalves; D. B. Jones (Kansas Agricultural Experiment Station Research Reports, 2018)
A study was conducted on a commercial sow farm to evaluate the effects of increasing dietary standardized ileal digestible (SID) lysine (Lys) intake in gestation on sow performance and piglet birth weight. A total of 936 females (498 gilts, 438 sows; Camborough, PIC, Hendersonville, TN) were group-housed (approximately 275 females per pen) and individually fed with electronic sow feeders (ESF). Scales were located in the alleyway after the feeding stations returning into the pen. Females were moved from the breeding stall to pens on d 4 of gestation and were allotted to 1 of 4 dietary treatments on d 5. Dietary treatments included increasing SID Lys intake (11, 13.5, 16, and 18.5 g/d). Gilts and sows received 4.6 and 5.1 lb/d, respectively, (5.3 and 5.7 Mcal NE/d) of feed throughout the entire study. Dietary treatments were achieved by different blends of low (0.48% SID Lys) and high (0.88% SID Lys) Lys diets via ESF based on the females’ set feed allowance. Initial and final BW and backfat were obtained on d 4 and 112 of gestation. Individual piglet BW was obtained within 12 h of birth on litters from 895 females. Data were analyzed using the GLIMMIX procedure of SAS. Body weight at d 112 of gestation increased within each parity group (linear,P<0.001) as SID Lys increased with gilts and sows consuming 18.5 g/d SID Lys weighing 16 and 11 lb more, respectively, than gilts and sows consuming 11 g/d SID Lys. There was no evidence for differences in d 112 backfat depth. Average total born for gilts and sows was 15.3 and 16.0, respectively with no evidence for differences among treatments. However, the percentage of pigs born alive increased (P= 0.006) with increasing SID Lys intake for sows but not in gilts. This is explained by the treatment × parity group interaction (P= 0.043) for percentage of stillborn pigs. In gilts, there was no evidence for differences among treatments in the percentage of stillborn pigs; however, in sows, as dietary SID Lys intake increased, the percentage of stillborn pigs decreased (linear,P= 0.002). Increasing SID Lys intake during gestation did not affect the percentage of mummified fetuses, total born, or born alive piglet birth weight in this study. In addition, increasing SID Lys intake during gestation did not affect subsequent reproductive performance. In conclusion, increasing dietary SID Lys intake in gestation increased female BW, without changing backfat or total born litter weight, indicating these females are depositing more lean tissue. The impact on female reproductive performance suggests that increasing SID Lys intake may increase the percentage of piglets born alive by reducing the number of stillborns in sows, but not in gilts.
Keywords: gilt; gestation; lysine; sow